A comparative study on the formation of heterocyclic amines and cholesterol oxidation products in fried chicken fiber processed under different traditional conditions. (May 2020) - Hsu, Kai-Yu; Chen, Bing-Huei
Abstract: This study aims to determine the formation of heterocyclic amines (HAs) and cholesterol oxidation products (COPs) in fried chicken fiber (FCF) processed under different traditional conditions. An ultra-performance liquid chromatography-mass spectrometry and gas chromatography-mass spectrometry technique was used to analyze various HAs and COPs respectively in chicken meat and FCF. Five HAs were produced in FCF during processing with the amount ranging from 0.052 to 106.005 ng/g and decreasing in the following order: 1-methyl-9H-pyrido[3, 4- b ]indole(Harman)>9H-pyrido[3, 4- b ]indole(Norharman)>2-amino-5-phenylpyridine(Phe-P-1)>2-amino-3-methyl-imidazo[4, 5- f ]-quinoxaline(IQx)>3-amino-1, 4-dimethyl-5H-pyrido[4, 3- b ]indole(Trp-P-1). Chicken fiber fried in lard at 180 °C/20 min generated a higher level of HAs (106.005 ng/g) than in soybean oil (77.823 ng/g), but with frying at 150 °C/40 min, the total HAs contents were reduced by 26.4% and 6.2% respectively. Seven COPs were produced in FCF with the maximum level being 35.220 μg/g and both cholesterol-5α-6α-epoxide (5, 6α-EP) and cholesterol-5β-6β-epoxide (5, 6β-EP) dominating. A lower level of COPs was formed in chicken fiber fried in lard (12.999 or 11.182 μg/g) than in soybean oil (35.220 or 28.553 μg/g) during frying at 150 °C/40 min or 180 °C/20 min, with the former reducing COPs by 77.9% without soy sauce. Comparatively, the formation of both HAs and COPs could be substantially reduced by processing FCF in lard at 150 °C/40 min without soy sauce flavoring. Highlights: Formation/inhibition of HAs & COPs in fried chicken fiber during processing were determined. HAs & COPs contents as affected by different oils, flavorings & temperatures were determined. A total of 5 HAs & 7 COPs were determined in fried chicken fiber. Harman & Norharman dominated in HAs, while 7α-OH & 7β-OH in COPs. Frying chicken fiber without soy sauce at 150 °C for 40 min reduced HAs & COPs.